Sentimen Analisis Terhadap Pembelajaran Jarak Jauh Menggunakan Metode Naïve Bayes Classifier dan Lexicon Based - Prianto, Cahyo; Hamka, Nurul Izza (Jurnal Ilmu Komputer, 2021)
Since the beginning of the COVID-19 pandemic, all fields have been affected, especially in the field of education, where the learning process is currently carried out remotely. This research was conducted to find out the responses from the community within the scope of education such as students, students and teachers. The number of respondents who gave their responses as many as 265 through filling out a questionnaire in the form of a google form. Based on this research, it is known that of the 265 people who responded with a total of 6 statements, then obtained 1,590 different answers. From 1,590 data were reprocessed so that the final data was 1,468. As for the results of labeling with this Lexicon based dictionary, 162 were positive, 516 were negative, and 790 were neutral. The test results with nave Bayes obtained an accuracy rate of 53.8% by using the measurement of the effectiveness of the confusion matrix.